Comparison of very high-intensity acceleration and deceleration in two professional élite football clubs (Serie C) across three seasons (2019-22) - Izzo, R.; Cejudo, A.; Giovannelli, M. (Journal of Physical Education and Sport, 2022)
This study aims to analyze and compare very high-intensity acceleration and deceleration in official matches in two different professional teams during three competitive seasons (Italian 3rd Division-Series C, 2019-20, 2020-21, 2021-22), to understand how two different training methodologies during the week influenced the performance about these parameters indicated above. Eighty-seven (n=87) élite football players participated in this study (age 23.1±1.4; body weight 77.8±1.7; height 181.9±0.6; fat mass 10.7±1.5), without goalkeepers. Every player has been analyzed with a K-AI live device 50Hz (K-Sport Universal STATS, Italy) in 857 pieces of training and 104 official matches for three regular seasons. These data were collected in groups with similar performance indexes (PI). All data have been analyzed with Dynamix Software, K-Sport Online. Data show that percentage very high intensity acceleration (%D_A8; >3m/s²) and very high intensity deceleration (%D_A1; < -3m/s²) are very large differences from during training session, respectively (ES: -1.63; p<0.05 and ES: -2.38; p<0.05) and during official match, respectively (ES: -2.11; p<0.05 and ES: 2.22 p<0.05). As regards the comparisons between seasons of the official competitions, there is an insignificant difference for all parameters between T1 and T2, which denotes a similar style of play and a similar level of preparation between the two seasons same athletic trainer and work volume physical between 32.9% and 35.4%. With an important all-out lactacid contribution without the ball in training 1 session per week for about 40 weeks. Instead between T1 and T3, the changes are statistically significant on all parameters in favor of T1 and between T2 and T3 in favor of T2. Also, this season the head fitness coach was the same but he worked between 7 and 10% less and the lactic acid work without the ball and with the ball was practically inexistent (0.07%).